# Two methods of calculating new average from old average

I know that calculating the new average $a_{new}$ from the old average $a_{old}$ can be done in the following way (for uniform weights):

Suppose the old average is based on $n$ elements. The old total is then $t_{old}=a_{old}\cdot n$. The new total is $t_{new}=t_{old}+x$. The new average is $a_{new}=\frac{t_{new}}{n+1}=\frac{a_{old}\cdot n + x}{n+1}$. (4 flops)

However, I found another way of calculating the new average $a_{new}$ from the old average $a_{old}$. I tried it numerical for some example, which is correct, but how can I prove it for all cases? My method is the following (also suitable for weights that are not uniform):

• Calculate the difference $d$ between the old average $a_{old}$ and the new element $x$ with $d=x-a_{old}$
• Multiply it with the weight $w$ of the new element $x$, so $q=d\cdot w$
• Add it to the old average $a_{old}$, so $a_{new}=a_{old}+q=a_{old}+(x-a_{old})\cdot w=x\cdot w + (1-w)\cdot a_{old}$.

The calculation $a_{new}=a_{old}+(x-a_{old})\cdot w$ has 3 flops

Which method is more efficient in terms of computing time? Or are they equally efficient?

• What is the weight? If it is $w=\frac{1}{n+1}$, then both methods you explain are equivalent (and equally efficient computationally, as none of them contains any loop). If by "weight" you mean something else, then they are not equivalent. – Anna SdTC Dec 15 '17 at 18:35
• $w$ is for example how much a certain item at school counts for the final mark, which is often known beforehand and not need to be calculated – Faceb Faceb Dec 15 '17 at 18:38
• All flops are not equal. Division is often nastier than all the others. – mathreadler Dec 15 '17 at 19:21
• If $w$ is some constant divided by an integer power of two you can make the second approach quite a bit faster. Yes 3 flops if we already know $w$, but are you sure $w$ will be constant? – mathreadler Dec 15 '17 at 19:30

\begin{align}a_{new}&=\frac{t_{new}}{n+1}\\&=\frac{a_{old}\cdot n + x}{n+1}\\ &= \frac{n}{n+1}a_{old}+\frac{1}{n+1}x\end{align}

The old formula requires one multiplication, two additions, and one division.

We have to set $w = \frac{1}{n+1}$ for the formula to be equal $a_{new}=a_{old}+q=a_{old}+(x-a_{old})\cdot w=x\cdot w + (1-w)\cdot a_{old}$

The new formula requires one subtraction, one division, one multiplication, and one addtion. The division is due to $\frac{1}{n+1}$.

Edit: consider data $x_1, \ldots, a_{n+1}$ with weight $w_1, \ldots, w_{n+1}$ \begin{align} a_{new} &= \frac{\sum_{i=1}^{n+1} w_ix_i}{\sum_{i=1}^{n+1} w_i} \\ &= \frac{\sum_{i=1}^{n} w_ix_i}{\sum_{i=1}^{n+1} w_i} + \frac{w_{n+1}x_{n+1}}{\sum_{i=1}^{n+1}w_i}\\ &= \frac{\sum_{i=1}^{n} w_ix_i}{\sum_{i=1}^{n} w_i} \left( \frac{\sum_{i=1}^{n} w_i}{\sum_{i=1}^{n+1} w_i}\right) + \frac{w_{n+1}x_{n+1}}{\sum_{i=1}^{n+1}w_i}\\ &= a_{old}\left( \frac{\sum_{i=1}^{n} w_i}{\sum_{i=1}^{n+1} w_i}\right) + \frac{w_{n+1}(x_{n+1}-a_{old}+a_{old)}}{\sum_{i=1}^{n+1}w_i} \\ &= a_{old} + \frac{w_{n+1}(x_{n+1}-a_{old})}{\sum_{i=1}^{n+1}w_i} \end{align}

• But the formula $a_{new}=a_{old}+(x-a_{old})\cdot w$ requires 3 flops right? (one addition, one subtraction and one multiplication) – Faceb Faceb Dec 15 '17 at 18:36
• what about computation of the weight? – Siong Thye Goh Dec 15 '17 at 18:38
• the weight is known beforehand, for example how much certain item at school counts for the final mark and therefore does not need to be calculated – Faceb Faceb Dec 15 '17 at 18:39
• $n+1$ is also known before hand for the first formula., you save one addition there. – Siong Thye Goh Dec 15 '17 at 18:40
• the first formula assumes uniform weight, which is why you can just sum them up and then divide by total number. – Siong Thye Goh Dec 15 '17 at 18:46